ANALISIS STRATEGI GURU DALAM MENGEMBANGKAN KARAKTER TANGGUNG JAWAB SISWA DI SDI MENI LONTONG - Frans Laka Lazar; Frans Sawan; Fanyo Armin Fitri; Maria Isabela Ndees; Rupertus Ardan Yunior (CREDENDUM: Jurnal Pendidikan Agama, 2026)
This study was motivated by the gap between the ideal expectations of student responsibility and the reality of behavior in the field. The phenomenon of low student responsibility at SDI Meni Lontong was identified through the inability to complete tasks on time, low interest in learning, and the negative influence of technology abuse. This problem requires pedagogical strategies that not only touch on cognitive aspects but also affective and psychomotor aspects so that the value of responsibility is transformed into spontaneous habits. The purpose of this study is to describe the strategies teachers use to instill responsible character, identify supporting and inhibiting factors, and formulate adaptive solutions to improve student academic discipline. This study uses a descriptive qualitative method with a postpositivist approach. Data were collected through observation, in-depth interviews, and documentation at SDI Meni Lontong. Data validity was tested through source and technique triangulation, while data analysis was carried out through the stages of reduction, presentation, and conclusion drawing. The results of the study show that teachers apply comprehensive strategies that include structured assignments, daily habituation mechanisms such as prayer and morning assemblies, and the integration of values into extracurricular activities such as scouting and sports. Other important findings highlight the role of teachers as living exemplars and the effectiveness of constructive responses through verbal appreciation in strengthening student motivation. The study concludes that character building in responsibility is successfully achieved through the integration of academic discipline, environmental hygiene management, and active collaboration with parents, thereby creating a transformative educational ecosystem for students' intellectual, emotional, and moral dimensions.